The effect of plasticizers and moisture on the pressing process and the properties of ceramic products based on zirconium dioxide - Ghyngazov, S.A.; Vasiliev, I.P.; Gyngazov, A.S.; Karabekova, D.Zh. (Russian Physics Journal, 2021)
An extensive application of zirconia ceramics in science and technology is determined by its unique properties, such as thermal stability, high hardness and chemical inertness. The latter property is widely used in the production of bioceramics [1]. Zirconia ceramics (ZC) due to its polymorphism does not exhibit high mechanical strength; therefore stabilizing [2] and strengthening [3] additives are introduced to improve it. In order to increase the mechanical strength, new composites are designed, for instance, 80ZrO2–20Al2O3 [4]. New potentials in improving the quality of ZC are offered by the use of nanopowders. The world leader in the production of the latter is Tosoh Corporation (Japan). Its initial products are used to manufacture fine-grained ZC with a density close to the theoretical value [5, 6]. The compacting pressure of 70 MPa, recommended by the manufacturer, is considerably lower than the minimal pressure, which could be provided by most laboratory compacting devices; therefore it is difficult to produce quality ceramics with them. At an unreasonably high pressure, there is an increase in the wall pressure and internal stresses in the bulk of the compact. A large amount of gases is observed inside it. All these factors give rise to fracture of the compacts and cracking of the ceramics during its sintering. The wall pressure can be reduced by lubricating the press molds or by introducing microadditives [7, 8] or plasticizers, such as epoxy resin, into the raw powder material [9]. There are available data on a positive influence of moisture on the characteristics of optical ceramics made of aluminum-yttrium garnet [10] and on the production of alumina-silicate ceramics using semidry molding of compacts [11, 12]. There are practically no results on the investigation of the influence of the above factors on the manufacture and properties of high-density zirconia ceramics reported in the literature for the initial zirconium dioxide nanopowder. In the present work, for the partially stabilized zirconia (PSZ) we study the influence of lubrication of the pressmold surfaces and introduction of plasticizing agents and moisture on the quality of the ceramics manufactured by sintering of the powder compacts formed by the method of uniaxial static pressing at a pressure of 120 MPa.
Keywords: zirconia; nanopowder; pressing; plasticizer; moisture